2009
DOI: 10.1111/j.1540-8191.2008.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Myxoma: A Case Report and a Collective Review of the Literature

Abstract: Tricuspid valve myxoma is extremely rare. An asymptomatic young patient discovered by chance an echogenic mass on the tricuspid valve by echocardiography, which was proved to be a myxoma. He underwent a successful myxoma resection via port-access approach. He had an uneventful postoperative course. Port-access approach is an alternative to conventional open heart surgical technique in terms of its minimally invasive purpose for myxoma resection. Moreover, it is of great importance in reducing the risk of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Two-thirds of the mitral myxomas are solitary and one-third is multiple ( 32 ). Tricuspid valve myxomas have a lower incidence, and even sporadic cases have been instantly reported ( 33 ). Aortic valve myxomas are even rarer ( 34 ).…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Two-thirds of the mitral myxomas are solitary and one-third is multiple ( 32 ). Tricuspid valve myxomas have a lower incidence, and even sporadic cases have been instantly reported ( 33 ). Aortic valve myxomas are even rarer ( 34 ).…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Myxomas have been reported to arise from the mitral valve apparatus [15], tricuspid valve, pulmonary artery and vein, and vena cava [1618]. In a review of 49 patients with cardiac myxoma, 6.1% arose from the mitral valve [19].…”
Section: Resultsmentioning
confidence: 99%
“…In a collective review, only 51 cases of myxoma originating from the TV were reported by 2008. Most tumors that originated from the TV required TV repair or replacement and myxoma resection (replacement, 22%; repair, 56.1%; tumor resection only, 22%) [2,3]. The tumor size varies from 1 to 15 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%